Guide to the Pianist's Repertoire, Fourth Edition - Hinson, Maurice (Book collections on Project MUSE., 2014)
This book serves as a resource for piano performers, teachers, and students. Updated and expanded with more than 250 new composers, this edition guides readers to solo piano literature and provides answers to common questions: What did a given composer write? What interesting work have I never heard of? How difficult is it? What are its special musical features? How can I reach the publisher? New to this edition are enhanced indexes identifying Black composers, women composers, and compositions for piano with live or recorded electronics; a listing of anthologies and collections organized by time period and nationality, now including collections from Africa and Slovakia; and expanded entries to account for material, works, and resources that have become available since the third edition, including websites and electronic resources.